The Influence of Water Temperature on Brewing of Coffee - Afif, Fuadi; Damasdino, Fian; Anwari, Hamdan (Gastronary, 2023)
The goal of this study is to determine whether or not the influence of water temperature has an impact on how Gayo Arabica coffee is brewed using the Anaerobic Cherry Maceration Process. Refractive index, extraction, total dissolved solids, and Yield are variables that are seen in the steeping effect. By contrasting the three differences in water temperature, 80°C, 90°C, and 100°C, this study employs an experimental methodology. According to this study's findings, there is a significant difference between 100oC, 90oC and 80oC in terms of the Ext parameter and Total Dissolved Solids. Other factors, like refractive index and Yield at the three temperatures, do not differ all that much.